Identification methods of the Royal Air Force Missing Research and Enquiry Service, 1944-52. (January 2021) - Hadaway, Stuart
Abstract: In 1945, the British Air Ministry established the Royal Air Force (RAF) Missing Research and Enquiry Service, to trace all of the RAF's wartime overseas casualties. Although a broad range of search techniques were used to find the resting places of personnel who were either known to have been killed or listed as missing, positive identification remained largely contingent upon an exhumation of their remains. This paper explores the forensic pathology and forensics techniques known to and used by the Search Officers involved.